Enterprise compliance risk management : an essential toolkit for banks and financial services - Ramakrishna, Saloni P., 1957- (Hoboken : Wiley, 2015)
'The tools and information that build effective compliance programs Enterprise Compliance Risk Management: An Essential Toolkit for Banks and Financial Services is a comprehensive overview of managing compliance and compliance risk. With unique hands-on tools including templates, checklists, and scorecards, practitioners can immediately begin to jumpstart compliance initiatives. Written from a real-world perspective, the book goes beyond theory to describe the practical aspects of active compliance management from all facets. Compliance professionals aren't the only stakeholders in active risk management. These concerns involve the various strata of management within the organization, regulators, industry bodies, and customers. Although a young and evolving discipline, compliance risk management is being brought to center stage as the complexity of the financial world increases exponentially, layering nuance and dimension on to an already complex topic. Enterprise Compliance Risk Management meets the need for a comprehensive reference, providing a framework for keeping up-to-date with the multitude of diverse legal requirements and guidelines bankers face. Topics include: Active compliance management as a strategic intervention Connections to reputation, legal risk, governance, and customer satisfaction The entire ecosystem of stakeholders outside of designated compliance officers Operation, training, and reporting of various compliance models The book also includes a direct examination of'risk', including identification, measurement, mitigation, monitoring, remediation, and regulatory dialogue, and an exploration of multidimensional financial services that points out focal points for active compliance management. Compliance professionals seeking a handle on this vital but fledgling discipline can find the information they need in Enterprise Compliance Risk Management'--
'The book provides banks and the financial industry with a comprehensive overview of compliance risk and its active management'--
Introduction to Compliance in Financial Services -- Part One: Introduction to Compliance in Financial Services. An Overview of Compliance in Financial Services -- Compliance in the Twenty-First Century -- The What, Why, and Who of Compliance -- Part Two: The What, Why, and Who of Compliance. What Is'Compliance'? -- Why Is Compliance Needed? -- Who Are the Players in the Compliance Universe? -- The How of Compliance -- Part Three: The How of Compliance. Compliance Framework -- Operationalizing Compliance -- The Compliance Risk Dimension -- Part Four: The Compliance Risk Dimension. Exploring the Concept of Compliance Risk -- Compliance Risk Management -- The Real World of Compliance in Financial Services -- Part Five: The Real World of Compliance in Financial Services. Real-Life Issues of Managing Compliance in Financial Services -- Lessons Not Learned -- Practical Solutions to Some Important Operational Challenges .
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Financial services industry -- Management; Business enterprises -- Law and legislation; Risk management; BUSINESS & ECONOMICS / Auditing; Business enterprises -- Law and legislation; Financial services industry -- Management; Risk management; Electronic books; Electronic books